The Role of Human Resource Management, Digital Technology, and Organizational Innovation in Optimizing Financial Management in Technology Start-Ups - Sundari, Sri; Djati , Pantja (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This research explores the influence of Human Resources Management (HR), Digital Technology, and Organizational Innovation on Optimizing Financial Management in the context of technology start-ups. Using the regression analysis method to test the hypothesis, this research found that these three elements have a positive and significant influence on financial management. The synergy between effective HR management, adoption of digital technology and organizational innovation has been proven to increase the efficiency and effectiveness of financial management. Good HR management contributes to increased innovation and adoption of digital technology, while digital technology supports the efficiency and accuracy of financial management through automation and data analysis. Organizational innovation helps companies offer unique value and differentiate themselves from competitors. This research also identifies that external factors such as market conditions and regulations can significantly influence financial results. These findings contribute to the development of managerial theory and practice by demonstrating the importance of an integrated approach that combines all three elements to achieve optimal financial management. This research provides strategic guidance for companies, especially technology start-ups, to design policies and strategies that support better financial management through synergy between HR, digital technology and organizational innovation.